Moment Analysis In Biometric-Based Authentication Systems - Pang, Ying Han (2005)
The competitive demand of accurate and stable automated identity authentication solutions and the acceleration of information technology have outcome an expeditious growth of biometric-based personal authentication system. We propose a novel cancelable biometric approach, known as Discrete hashing, to solve the irrevocable biometric puzzle. The proposed method conceals biometric template with a set of random number via orthonormalized inner product operation to obtain a set of binary code.